Sequential cyclic changes of hair roots revealed by dermoscopy demonstrate a progressive mechanism of diffuse alopecia areata over time. Issue 3 (5th December 2018) - Zhang, Xingqi; Ye, Yanting; Zhu, Zhaohui; Yang, Yuqing; Cao, Hui; McElwee, Kevin J.; Ling, Yunxia
Abstract: Background: Diffuse alopecia areata (DAA) often leads to a complete hair shedding within a few months. Objective: To explore features and mechanisms underlying DAA. Materials and Methods: Scalp and hair root dermoscopy were conducted on 23 DAA patients throughout the disease process, 20 patchy Alopecia areata patients, 23 acute telogen effluvium (ATE) patients and 10 normal controls. Histopathology was also evaluated. Results: We found almost all hair roots were anagen in early stage DAA in 18 patients (18/23, 78.3%) within the first 4‐8 weeks after hair loss onset. Anagen effluvium (~4 weeks) was followed by catagen (~4 weeks) and then telogen/exogen (~8 weeks) effluvium with overlap. Hair root and proximal hair shaft depigmentation was more prominent in later DAA disease stages. Black dots, exclamation mark hairs and inconsistent thickness of hair shafts were found more often in early than later DAA ( P s < 0.01). Early DAA histopathology revealed more prominent inflammation and hair follicle regression than that observed in the later stages. Patchy alopecia areata patients showed mixed anagen, catagen and telogen hair roots while ATE patients showed increased exogen and mildly decreased hair root pigmentation. Conclusion: Sequential cyclic staging of shed hairs in DAA indicates the insult may be hair‐cycle specific. We suggest that DAA is initially an anagen effluvium disease involving an intense inflammatory insult, later progressing to a brief catagen effluvium, and then to telogen effluvium with premature exogen, in later stages of DAA.